Proximate Nutritional Composition of Acacia auriculiformis A. Cunn. Seeds - Singh, Pankaj; Kumar, Ashwani; Ansari, Shamim Akhtar; Singh, Sanjay (Indian Forester, 2018)
Proximate nutritional value of Acacia auriculiformis seeds for their protein, total carbohydrate, oil content and energy value was estimated aiming at its utilization to meet the requirement of daily food needs of tribal and local people during food scarcity. It was found that A. auriculiformis seeds have protein 8.47 ±0.98%, total carbohydrate 39.98±4.33%, lipids 8.12±0.41% and total energy kcal/100g 346.90 ±7.51suggesting their suitability to use as an alternative source to traditional staple food especially for marginalized tribal populations with a limited access to conventional cereals and pulses.